Numerical analysis of isolated end-flattened steel bars under compression in space trusses - Henrique de Araujo Rosa Cruz; Luciano Mendes Bezerra; Welington Vital da Silva; Ramon Silva (Fracture and Structural Integrity)
This research aims to characterize the behavior of isolated end-flattened steel bars under compressive loading, in which global instabilities or excessive local deformations represent a significant part of the causes of structural collapse. The association of numerical analyses using the finite element method (FEM) with previously collected experimental data is performed, and their respective results are the core object of critical analysis in this work. Numerical simulations are based on the modified Riks method, complemented in part by modal analysis, whose results demonstrate the occurrence of the aforementioned failure modes in prototypes with slenderness ratios varying in the spectrum from 20 to 200. Finally, the analytical formulations that describe the phenomenon from the approach of global and local instabilities incorporated into current normative expressions are applied in a comparison with the results gathered in the numerical approach.